Authors of “Wireless Textile Moisture Sensor for Wound Care” Misinformed - Benskin, Linda L. (Frontiers in Physics, 2022)
The researchers who conducted the study described in Wireless Textile Moisture Sensor for Wound Care (Tessarolo, et al.) seem to have been misinformed. In the abstract, they state, “Currently, clinicians monitor the wound’s status by removing the dressing, disturbing the healing process. A relevant parameter that they need to monitor is wound moisture.” The need to remove the dressing to monitor the wound's moisture status is true when clinicians use most conventional dressings. However, several “indicator dressings” exist, including all PolyMem dressing configurations and Allevyn Life (1,2,3,4). These dressings all change colors to indicate when they have absorbed enough moisture that they should be changed. PolyMem, which is a polymeric membrane dressing, is an indicator dressing that also balances moisture across the wound bed, absorbing moisture from overly wet areas while simultaneously donating moisture to overly dry areas (1,2,4). Clinicians using these dressings remove the dressing only when it is ready to be changed, because they can monitor the wound’s moisture status by looking at the dressing backing (1,2,3,4).